Dapansutrile Regulates Mitochondrial Oxidative Stress and Reduces Hepatic Lipid Accumulation in Diabetic Mice - Ying Wu; Jiaqiang Zhou (Current Issues in Molecular Biology)
(1) Background: Hepatic lipid accumulation is the initial factor in metabolic-associated fatty liver disease (MAFLD) in type 2 diabetics, leading to accelerated liver damage. The NOD-like receptor protein 3 (NLRP3) inflammasome plays a critical role in this process. Dapansutrile (DAPA) is a novel NLRP3 inflammasome inhibitor; however, its effect on ectopic lipid accumulation in the liver remains unclear. This study aimed to investigate the therapeutic effect of DAPA on hepatic lipid accumulation in a diabetic mouse model and its potential mechanisms. (2) Methods: The effects of DAPA on hepatic ectopic lipid deposition and liver function under metabolic stress were evaluated in vivo using db/db and high-fat diet (HFD) + streptozotocin (STZ) mouse models. Additionally, the role and mechanism of DAPA in cellular lipid deposition, mitochondrial oxidative stress, and inflammation were assessed in HepG2 cells treated with free fatty acids (FFA) and DAPA. (3) Results: Our findings indicated that DAPA treatment improved glucose and lipid metabolism in diabetic mice, particularly addressing liver heterotopic lipid deposition and insulin resistance. DAPA treatment also ameliorated lipid accumulation and mitochondrial-related functions and inflammation in HepG2 cells through the NLRP3-Caspase-1 signaling axis. (4) Conclusions: Targeting NLRP3 with DAPA may represent a novel therapeutic approach for diabetes-related fatty liver diseases.